Development of the Catastrophe Bonds and their correlation with other financial instruments - Čavojec, Ján; Hnilica, Jiří, 1976-; Varvařovský, Václav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
This master thesis discusses the niche of reinsurance business -- catastrophe bonds. It provides a brief description of reinsurance in general, insurance-linked securities and catastrophe bonds. The goal of this thesis is to describe the development of cat bond market and the influence of economic and natural shocks on it. In order to analyze the effect, quarter issuance data are used together with Swiss Re Cat Bonds return indexes. In addition, several other variables (i.e. Munich Re and Swiss Re stock prices) and indexes are used. The most important indexes are Merrill Lynch high yield bonds and structured products. The shocks' influence is examined by analyzing the correlation between cat bonds yields and other financial instruments. The conclusion of the thesis is that during economic boom cat bonds are correlated with other instruments. In times of recession cat bonds' yields prove to be negatively or not correlated with other negatively affected instrument.
Vedoucí práce: Jiří Hnilica
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses